2007
DOI: 10.1103/physrevb.76.054116
|View full text |Cite
|
Sign up to set email alerts
|

Two-phonon infrared spectra of Si and Ge: Calculating and assigning features

Abstract: Third-order density-functional perturbation theory yields the terahertz and/or far-infrared absorption spectra for silicon and germanium, including all two-phonon combination and difference features. Temperaturedependent spectra are compared to available experimental results. Critical-point analysis is used to identify the branch and wave-vector indices of many features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…(a) and are significant below 100 K and dominant below 50 K. The value of the loss tangent measured at the large field of 5 × 10 4 G apparently have thus quenched the loss component from electron paramagnetic resonance and our results do not give additional insight into the mechanism of this component of loss. Earlier researchers have concluded that losses arise from mechanisms such as free carrier and polaron absorption, anharmonic‐phonon absorption, and precession of electric dipoles in polar molecules . The peak observed in the loss tangent at ~100 K in some of the samples appears to be similar to that typically attributed to polaron conduction …”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…(a) and are significant below 100 K and dominant below 50 K. The value of the loss tangent measured at the large field of 5 × 10 4 G apparently have thus quenched the loss component from electron paramagnetic resonance and our results do not give additional insight into the mechanism of this component of loss. Earlier researchers have concluded that losses arise from mechanisms such as free carrier and polaron absorption, anharmonic‐phonon absorption, and precession of electric dipoles in polar molecules . The peak observed in the loss tangent at ~100 K in some of the samples appears to be similar to that typically attributed to polaron conduction …”
Section: Resultsmentioning
confidence: 59%
“…To date, researchers have identified a number of mechanisms that can cause microwave loss in dielectrics, including free carrier and polaron absorption, EPR, anharmonic‐phonons, and precession of electric dipoles in polar molecules …”
Section: Introductionmentioning
confidence: 99%
“…ELF in phonon regime Si 6K data from [88] 6K calculation from [90] Ge 2K data from [89] 6K calculation from [90] GaAs 10K calculation of [79], combined with [80] Al2O3 Analytic model, using data from [87,91] α−SiO2 Analytic model, using 300K data from [81] GaN Analytic model, using 300K data from [92] ZnS Analytic model, using 300K data from [93] SiC Analytic model of [83], with data from [94] TABLE I. Sources of the ELF in the phonon regime, for different materials.…”
Section: Methodsmentioning
confidence: 99%
“…We show the result of optical measurements at 6K for Si [88] and at 2K for Ge [89]. The dotted lines show the result of DFT calculations done assuming a temperature of 6K [90].…”
Section: Im[-1/ (ω)]mentioning
confidence: 99%
“…Figure 2 shows the transmittance of the retarder between 20 -250 cm −1 , measured at room temperature. Above ∼100 cm −1 the two-phonon absorption in silicon [23] reduces significantly the system's overall transmittance.…”
Section: Retarder Performancementioning
confidence: 99%